Diplomasi Budaya Jepang Melalui Penyelenggaraan Bali Japan Matsuri di Indonesia - Chandra, Arditya Sukma; Kumala Dewi, Putu Ratih; Intan Prameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT The development of the world now a days has made traditional diplomacy shifts to become more modern. This also means that there would be more instrument that diplomacy can use for it’s track, which is one of the instrument is cultural aspect. The Japanese government through Bali Japan Matsuri hopes to introduce more of Japan's popular culture and enhance its positive image in Indonesia as a target country. This study aims to provide an explanation of how Japan uses its popular culture as an instrument of diplomacy to provide a positive image to the Indonesian nation, and the purpose of this study will also present a descriptive analysis of the values contained in the Bali Japan Matsuri festival through the concept of soft power currencies. Keywords : Bali Japan Matsuri, Pop Culture, Soft Power Currencies